Controlling natural resources depletion through Montmorillonite replacement for cement-low cost construction. (30th January 2020) - Rehman, Safi Ur; Kiani, Usman Ahmed; Yaqub, Muhammad; Ali, Tariq
Highlights: Karak Montmorillonite (K-M) fulfil all the requirements to be used as natural pozzolana. Karak Montmorillonite (K-M) clay can be used as Supplementary cementitious material for low cost concrete. Initial and final setting time are increased by using K-M clay as cement replacement. Porous structure of the concrete can be improved by incorporating K-M clay. K-M can improve the durability properties of concrete against chemical attacks. Abstract: This research is aimed to evaluate Montmorillonite clay (commercially known as Bentonite clay) available in Karak, 33°7′12′′ N 71°5′41′′ E, (KPK, Pakistan) as cement replacement material. In this study the clay was incorporated (5%, 10%, 15%, 20%, and 25%) by mass of cement keeping other constituents of concrete constant. The morphology of Karak-Montmorillonite was studied using Scanning Electron Microscope (SEM). All samples of K-M satisfied the Strength Activity Index (SAI) requirements of ASTM C 618. Results revealed that workability of concrete decreased with an increase of K-M content. Consequently, initial and final setting time was increased. The mechanical compression and Non-destructive testing (NDT) were performed to evaluate the compressive strength. The results disclosed that increase in K-M content significantly reduced the compressive strength. Concrete with 15% K-M gave competent results relative to control mix. The tensile and flexural strength of concrete also decreased with the increase of K-M content. Concrete with K-M as replacement for cement showed better performance in durability tests i.e. water absorption, permeability, acid attack, sulphate attack, carbonation test and pH test. Acid and salt cured samples containing K-M performed better than normal control samples. Utilization of the Karak-Montmorillonite (K-M) as cement replacement is low-cost, eco-friendly and produce durable concrete.